The Development of the Postpartum Depression Self-Management Mobile Application "Happy Mother". Issue 8 (August 2021) - Seo, Ji Min; Kim, Su-Jeong; Na, Hyunjoo; Kim, Jin Hee; Lee, Hyejin
Abstract : Postpartum depression is the most common mood disorder that occurs after childbirth, rendering it a significant public health problem. Information and communication technologies hold tremendous promise for expanding the reach of quality mental healthcare and closing the treatment gap for depression. In particular, given that mobile applications are inexpensive and provide information systematically, they are suitable as a method of health management that does not require visiting a medical center. The purposes of this study were to document the process of developing a mobile application for the self-management of postpartum depression and to share usability test results. The mobile application "Happy Mother" was developed based on the first five of seven stages in the mobile application development lifecycle model. Components of cognitive behavioral therapy were adopted to guide content development for "Happy Mother." The usability of the completed mobile application was tested in the following three steps: it increased awareness of mood, promoted self-management, and implemented specific methods a mother can use in her daily life to improve mood, including modifications made based on the results of the usability test.